A Study of EFL Students’ Cultural Awareness in Learning at English Department of Universitas Muhammadiyah Bone - Larawi, Nurul Ashiqin Binti; Atmowardoyo, Haryanto; Iskandar, Iskandar (Celebes Journal of Language Studies, 2023)
This research aims to find out students’ cultural awareness when learning English and the impact of cultural awareness on English language learning. The researcher conducted this research at the Universitas of Muhammadiyah Bone. The method of this research is descriptive-qualitative research. The research instruments employed were an interview and a questionnaire. The data were collected using a questionnaire with a Google Form and interview techniques. The research participants were English Department student at the sixth-semester of Universitas Muhammadiyah Bone. The results of this study indicated that the majority of EFL students have an awareness of their culture during the learning process and students also showed that their reactions to culture are related to cultural knowledge. In addition, students' responses indicated that cultural awareness is very important for developing positive attitudes towards people who have different cultural values, beliefs, and behaviors. The results also showed that the relationship between culture and linguistics is closely intertwined and influences each other, and the findings showed cultural awareness had positive impact to learning English on EFL students at Universitas Muhammadiyah Bone.